Rhizopus-host interplay of disseminated mucormycosis in immunocompetent mice - Dos Santos, Amanda R. [UNESP]; Fraga-Silva, Thais F. [UNESP]; Almeida, Débora de F [UNESP]; Dos Santos, Rodolfo F. [UNESP]; Finato, Angela C. [UNESP]; Amorim, Bárbara C [UNESP]; Andrade, Maria I.; Soares, Cleverson T.; Lara, Vanessa S.; Almeida, Nara Lm; de Arruda, Olavo S. [UNESP]; de Arruda, Maria Sp [UNESP]; et al. (Taylor & Francis, 2020)
Aim: To investigate the immune response of disseminated Ryzopus oryzae infection in immunocompetent mice. Methods: C57Bl/6, BALB/c and Swiss wild-type mice were intravenously infected with R. oryzae; the parameters of infection and immune response were determined. Transcriptional signature of Th17 immune response and infection in Il17ra-/- mice were also evaluated. Results: All mouse strains showed an initial spread of R. oryzae in the target tissues; however, after 30 days, C57Bl/6 and BALB/c mice showed an effective fungal clearance associated with specific production of IL-17 and IL-2. We also observed that 60% of Il17ra-/- mice succumbed to infection within 16 days. Conclusion: This study has established an immunocompetent model for disseminated mucormycosis and highlighted the role of IL-17 signaling in immunity against R. oryzae.
Keywords: BALB/c; C57BL/6; cytokines; IL-17; Il17ra-/-; il6; immunocompetent model; intravenous infection; mucormycosis; Rhizopus oryzae; rorc; Swiss